Prevalence of self-medication and its associated factors: a case study of Kurdistan province. Issue 3 (21st February 2020) - Ghaderi, Ebrahim; Hassanzadeh, Kambiz; Rahmani, Khaled; Moradi, Ghobad; Esmailnasab, Nader; Roshani, Daem; Azadnia, Arian
Abstract : Purpose: Health is one of the most basic human rights. Self-medication not only results in many risks, complications and mortalities but also remains a massive economic burden on governments' pharmaceutical budgets, insurance companies and the general population. The importance of self-medication as one of the worldwide health problems, this paper aims to investigate the extent of this problem and related factors in Sanandaj, Iran in 2018. Design/methodology/approach: This cross-sectional, descriptive study was conducted on 838 people who referred to pharmacies in Sanandaj, Iran in 2018. The subjects were selected in 10 pharmacies, 84 in each, randomly. A self-constructed questionnaire was used to collect information about demographic features, prevalence and reasons for self-medication. The data was analyzed statistically by SPSS software. Findings: The results show a high prevalence of self-medication, 73.70 per cent among people who referred to the pharmacies in Sanandaj during 2018. There was a significant correlation between self-medication and occupation, education level, age groups, chronic disease, smoking or reasons to refer to pharmacies (p < 0.05). Analgesics, antibiotics; non-steroid anti-inflammatory, cold and gastrointestinal medicines were the most commonly used medicines by the subjects. People with headache, cold, infection, stomach pain, toothache and dysmenorrhea were more likely to act self-medication than people with other complaints. Among people who do self-medication, (85.60 per cent) had already experienced satisfactory results after using medicines. Mild symptoms of the disease (74.11 per cent), availability of medicines (72.98 per cent) and easy access to medicine supplies in pharmacies (71.35 per cent) are other reasons for self-medication. Research limitations/implications: In general, the study had some limitations. One of the limitations was related to the research period i.e. spring and summer. So, it is suggested to conduct studies in other seasons, too. Furthermore, as the time of self-medication was the past three months, there was a probability of recall bias. Originality/value: The prevalence of self-medication in Sanandaj is high and alarming, implementing educational programs about this issue is extremely required. Health policymakers should take all necessary steps to tackle self-medication efficiently.